PointSampler: A GIS Tool for Point Intercept Sampling of Digital Images - Gobbett, David Lyon; Zerger, Andre (Biodiversity Informatics, 2014)
Close-range digital photography to assess vegetation cover is useful in disciplines ranging from ecological monitoring to agricultural research. An on-screen point intercept sampling method, which is analogous to the equivalent field based method, can be used to manually derive the percentage occurrence of multiple cover classes within an image. PointSampler is a GIS embedded tool that provides a semi-automated approach for performing point intercept sampling of digital images, and which integrates with existing GIS functionality and workflows. We describe and illustrate the two general applications of this tool, in in efficiently deriving primary ecological data from digital photographs , and for the generation of validation data to complement automated image classification of a time series of groundcover images.  The flexible design and GIS integration of PointSampler allows it to be put to a wide range of similar uses.